Mobilizing Revenue in Sub-Saharan Africa : Empirical Norms and Key Determinants - Drummond, Paulo; Daal, Wendell; Oliveira, Luiz.; Srivastava, Nandini (Washington, D.C. : International Monetary Fund, 2012)
Mobilizing more revenue is a priority for sub-Saharan African (SSA) countries. Countries have to finance their development agendas, and weak revenue mobilization is the root cause of fiscal imbalances in several countries. This paper reviews the experience of low-income SSA countries in mobilizing revenue in recent decades, with two broad aims: identify empirical norms of how much and how fast countries have been able to mobilize more revenue and empirical determinants (panel estimates) of revenue mobilization. The paper finds that (i) the frequency distribution of changes in revenue ratios for SSA low-income countries (LICs) peaks at a pace of about 1\2 -2 percentage points of GDP in the short-to-medium term and at a pace of about 2-3 1\2 percentage points of GDP over the longer term, and that (ii) almost all SSA-LICs managed to increase revenue ratios by more than 2 percentage points of GDP in the short-to-medium term, at least once in the last two decades. The sustainability of large increases in revenue ratios can be an issue, in particular for fragile countries. The panel estimates suggest that structural factors, such as per capita GDP, share of agriculture in GDP, inflation, degree of openness, and rents received from natural resources, are important determinants of tax revenue.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet